Enhancing Students’ Digital Creativity through TikTok Augmented Reality Filter Development: A Community Service Study at SMKN 1 Manggis (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
This study reports a community service program aimed at enhancing students’ digital creativity through Augmented Reality (AR) filter development using TikTok Effect House. The program involved 35 students from SMKN 1 Manggis and employed an interactive workshop approach consisting of lectures, demonstrations, hands-on practice, and mentoring.The results indicate a positive increase in students’ understanding of AR concepts and technical skills, as reflected in evaluation scores ranging from 4.20 to 4.43 on a 5-point Likert scale. Students were able to independently create AR filters and produce digital portfolio outputs. These findings suggest that practice-based AR training can support the development of students’ creative and technical competencies, while also encouraging more productive use of social media in line with the needs of the digital creative industry.